#TITLE_ALTERNATIVE# - PATRICIA GINTING (NIM : 13605031); Pembimbing: Dr. Hari Muhammad, DELLA
At a determined flight conditions, aircraft getting interference from the surrounding environment such as wind turbulence, air density variation, and other external disturbances. In order to fly the aircraft at the determined flight condition, the force and moment balance is required so that the aircraft can achieve static stability conditions. In operational terms, the balance condition of the aircraft is called trim condition where all forces and moments acting on the aircraft mutually exclusive. Trim parameters that analyzed on longitudinal flight mode are angle of attack (α), elevator deflection (δe), and thrust. In the calculation of trim equations of motion, substitution of the equations of motion at longitudinal dimension is needs to be done first. Force and moment components are used to initiate programming procedures performed on the coordinates of reference objects. After obtaining the trim equations of motion on the reference coordinate system objects and then performed a simulation in Matlab software. Simulations carried out in several flight conditions, namely flying speed (70 - 150 m/s), aircraft mass (5.000 kg, 5.500 kg, and 6.000 kg), and flying altitude (1.500 m, 3.500 m and 5.500 m). From the simulation results, the value of α and the thrust will be even greater if the mass of aircraft is heavier and the higher altitude, otherwise the faster flying speed, the thrust value of α and thrust will be smaller. Whereas the value of δe parameter will be even greater if the mass of aircraft is heavier, faster flying speed, and higher altitude.